Fortificações e povoamento no Norte de Portugal (séc. IX a XI) - Barroca, Mário Jorge (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The author characterizes the time when the first castles were built in the North of Portugal during the last three decades of the 9th century (circa 870-900) and correlates this event to the Christian conquest process. The earliness of this process in the valley of river Douro is emphasized and the major evolution of the “encastelamento” (castle building) in the North of Portugal is presented, with identification of the 50 castles documented until the year 1000. Two major groups of military structures are identified: castles built by the Counts and castles built by the local communities. The author also characterizes the military process of the “Reconquista” (reconquest): first the progress up to river Mondego and the formation of the County of Coimbra (878); then the campaigns of alMansur and the Christian retreat to river Douro (986-997); finally, the definitive conquest of the Beiras (1057-1058) and Coimbra (1064). At last, the Author describes the new territorial organization of Terrae, due to Fernando Magno, which had crucial importance in the development of the Romanesque castles.